Habitat rehabilitation in the Detroit River Area of Concern. Issue 4 (2nd October 2018) - Hartig, J. H.; Sanders, C.; Wyma, R. J. H.; Boase, J. C.; Roseman, E. F.
Abstract : Loss and degradation of fish and wildlife habitat is a long-standing issue in the Detroit River. The Detroit River Remedial Action Plan helped agencies and stakeholder groups reach agreement on impaired beneficial uses, including loss of fish and wildlife habitat, and helped mobilize all stakeholders to rehabilitate habitat. Many organizations played key roles, including the Detroit River Public Advisory Council, Detroit River Canadian Cleanup, State of the Strait Conferences, American and Canadian Heritage River Initiatives, Detroit River International Wildlife Refuge, and Western Lake Erie Watersheds Priority Natural Area. Accomplishments include: 14 habitat restoration projects on both the Canadian and U.S. side of the Detroit River; 53 soft shoreline engineering projects in the watershed; nine fish spawning reefs in the river, Common Tern habitat in four locations; and many wetland and green infrastructure projects. Based on Detroit River habitat restoration efforts over the last 32 years, the following advice is offered: reach agreement on severity and geographic extent of the problem; practice adaptive management; involve habitat experts up front in project design; establish quantitative targets for project success; ensure sound multidisciplinary technical support; start with demonstration projects; treat habitat projects as experiments; involve citizen scientists in monitoring; measure benefits; communicate and celebrate successes; promote education and outreach.